Compliance of selected restaurant restrooms with Universal Design, Quezon City Gender Fair Ordinance and Accessibility Law - Tan, Anna Nazharina P.; Brasileño, Lynne I. (Quezon City College of Home Economics, University of the Philippine Diliman, 2015)
ABSTRACT Eating out has become a routine rather than an occasional event for a Filipino family because of the expansion of the middle class. Competition in the food business industry urged businessmen to come up with different marketing strategies to catch customer's attention. One of which is restaurant branding through cohesive design. This study intended to find out whether selected casual-dining restaurants in Quezon City complied with the requirements of the seven principles of Universal Design, Quezon City Gender Fair Ordinance (QCGFO) and the Accessibility Law or the Batas Pambansa 344 (BP 344), in contrast with the unique concept and branding used in each restaurant. This study also determined whether there is a correlation between compliance with design standards and the level of comfort of the users. Five key informants, which included a child, abled, disabled, pregnant and elderly, and three restaurant samples, were chosen using purposive sampling to narrow down results. Restaurant branding through cohesive design was observed in all selected casual-dining restaurants. However, branding was only seen on a surface level, meaning restaurant theme was shown only through accessories color scheme and motifs. Results also showed that despite having different concepts and themes, all four restaurant samples satisfactorily complied with the seven principles of Universal Design. Majority of the restaurant samples also complied with the QCGFO, providing unisex restrooms for the customers. On the assessment of BP 344, however, results showed a low percentage of compliance with the applicable provisions from the Accessibility Law. Considering the when using the space were quite high.
Thesis (B.S. Interior Design)--University of the Philippines Diliman.
Keywords: Restrooms -- Philippines; Restaurants -- Law and legislation -- Philippines